Analysis of the Effect of Earthquake Loads on the Response of Cable Stayed Bridges - Multilawati Nasution (Journal of Civil Engineering and Planning (JCEP), 2023)
Barella bridge is a type of cable stayed bridge in Indonesia. According to the cable arrangement pattern, cable stayed bridges are divided into three types, namely radial type, harp type, and fan type. On cable stayed bridges, dynamic analysis is needed so that the bridge is categorized as safe. One of the loads used in dynamic analysis is the earthquake load. Earthquake is a physical phenomenon characterized by vibrations on the earth's surface with various intensities. The earthquake itself is divided into two, namely horizontal earthquakes and vertical earthquakes. In this case study, the earthquake load is input for the padang area zone in the time history and the software used is SAP 2000 to calculate the response on both the girder and pylon. This research found the influence of vertical earthquake loads and horizontal earthquake loads on the response of cable stayed bridges, especially the displacement and tension of the cables.